2008
DOI: 10.1080/09602010701595136
|View full text |Cite
|
Sign up to set email alerts
|

Participant perspectives on an individualised self-awareness intervention following stroke: A qualitative case study

Abstract: Most research investigating the efficacy of neurorehabilitation has focused upon pre- versus post-intervention functioning, which is important for evidence-based practice but overlooks the therapeutic process. Therefore, this qualitative study aimed to investigate a participant's perspective of experiences in therapy throughout an awareness rehabilitation intervention. The participant(CP), a young male with awareness deficits following a right thalamic stroke,had repeatedly attempted to return to work and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Related to this point, the review focused on studies that employed quantitative methods to evaluate rehabilitation outcomes. Qualitative approaches, such as guided self-reflection within therapy sessions (e.g., Ownsworth, Turpin, Andrew, & Fleming, 2008) and in-depth interviews (e.g., Dirette, 2002;Kristensen, 2004), may provide greater scope to explore changes to self-understanding in the context of rehabilitation. The application of mixed methods (i.e., qualitative and quantitative approaches) to outcome evaluation in brain injury rehabilitation is relatively uncommon (see Kreutzer, Stejskal, Godwin, Powell, & Arango-Lasprilla, 2010;Turner-Stokes, 2008), and represents a promising approach to investigating changes to sense of self in future intervention studies.…”
Section: Review Limitationsmentioning
confidence: 99%
“…Related to this point, the review focused on studies that employed quantitative methods to evaluate rehabilitation outcomes. Qualitative approaches, such as guided self-reflection within therapy sessions (e.g., Ownsworth, Turpin, Andrew, & Fleming, 2008) and in-depth interviews (e.g., Dirette, 2002;Kristensen, 2004), may provide greater scope to explore changes to self-understanding in the context of rehabilitation. The application of mixed methods (i.e., qualitative and quantitative approaches) to outcome evaluation in brain injury rehabilitation is relatively uncommon (see Kreutzer, Stejskal, Godwin, Powell, & Arango-Lasprilla, 2010;Turner-Stokes, 2008), and represents a promising approach to investigating changes to sense of self in future intervention studies.…”
Section: Review Limitationsmentioning
confidence: 99%
“…Changing understanding of stroke recovery, brain plasticity, and motor learning has lead to novel treatment approaches [1], but client perception is often neglected in their development [2]. Given marked differences in the way interventions are viewed by therapists when compared with people living with stroke [3,4], incorporating client experience and knowledge in approach development is important for long-term success and eventual uptake [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested, however, that stroke recovery should be defined in the relation to the social context and personal goals of the person living with stroke [16,17], and that rehabilitation and clinical outcomes should include the perspective of people living with stroke [2,18,19]. In a 2004 review of qualitative stroke research, the authors concluded that despite flourishing research in all areas from basic science to novel intervention development, delivery of bestquality stroke care remains problematic [5].…”
Section: Introductionmentioning
confidence: 99%
“…The sample size and type varied between the studies. Twelve studies examined metacognitive function exclusively in patients with stroke 2 29 31 34–36 39 40 44 53 56 58. The remaining 22 studies consisted of other patient groups alongside stroke (eg, traumatic brain injury, tumour or hypoxic event).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies did not define the term 2 30–32 42 44 47. Sixteen studies made reference to a theoretical framework or model to describe a component of metacognition 5 6 20 29 33 34 37 40 46–48 50 51 53 54 58. The main theoretical framework discussed was Crosson et al 's three-level model of self-awareness.…”
Section: Resultsmentioning
confidence: 99%